2014
DOI: 10.1186/1743-8977-11-6
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of multi-walled carbon nanotubes at occupationally relevant doses

Abstract: Carbon nanotubes are commercially-important products of nanotechnology; however, their low density and small size makes carbon nanotube respiratory exposures likely during their production or processing. We have previously shown mitotic spindle aberrations in cultured primary and immortalized human airway epithelial cells exposed to single-walled carbon nanotubes (SWCNT). In this study, we examined whether multi-walled carbon nanotubes (MWCNT) cause mitotic spindle damage in cultured cells at doses equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
116
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 96 publications
12
116
2
Order By: Relevance
“…2B, middle panel, indicated by #). This finding is consistent with previous reports that exposure to MWCNT caused a G1/S block in cultured cells (Han et al 2012; Siegrist et al 2014). …”
Section: Resultssupporting
confidence: 94%
“…2B, middle panel, indicated by #). This finding is consistent with previous reports that exposure to MWCNT caused a G1/S block in cultured cells (Han et al 2012; Siegrist et al 2014). …”
Section: Resultssupporting
confidence: 94%
“…The deposited doses for the current study were selected to be in the range of 0.24-2.4 mg/cm 2 for occupationally relevant doses recently reported in studies in accordance to the permissible exposure limit of 1 mg/m 3 suggested by NIOSH (NIOSH, 2013;Porter et al, 2010;Siegrist et al, 2014). Sargent et al (2014) have performed an inhalation study with mice and exposed them with 5 mg/m 3 MWCNTs for 5 h per day, 5 d a week for 15 d and calculated a total deposited material concentration in the lungs to 0.06 mg/cm 2 mimicking a two week human occupational exposure scenario.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study concerning the potential toxicity of MWCNT showed that, although pathway-level cellular functions were similar between in vivo and in vitro experiments, microarray analysis determined different gene expression profiles between in vivo and in vitro models (Sos Poulsen et al 2013). MWCNT induce numerous deleterious effects in mouse lungs after both aspiration and inhalation exposures (Mercer et al 2011; Mercer et al 2013; Porter et al 2013; Porter et al 2010; Sargent et al 2014; Siegrist et al 2014), and the ability to reflect these effects in vitro with an accurate transcriptomic profile remains difficult. Although in vitro global gene expression and microarray analysis may be useful for providing a generic overview of responses, cellular signaling from chronic exposure in vivo and acute signaling in vitro may produce different expression results (Klaper et al 2014).…”
Section: Introductionmentioning
confidence: 99%